Castle Adventure for pre-primary - Hunt,Roderick (Oxford University press, 1986)
"ORT Castle Adventure" by Roderick Hunt is a story from the Oxford Reading Tree series. In this tale, the main characters$1 (BBiff, Chip, Kipper, and their dog, Floppy$1 (Bembark on an exciting adventure at a castle.s
Keywords: Textbook